Through an Indian's looking-glass : a cultural biography of William Apess, Pequot - Lopenzina, Drew (Native Americans of the Northeast., 2017)
"The life of William Apess (1789-1839), a Pequot Indian, Methodist preacher, and widely celebrated writer, provides a lens through which to comprehend the complex dynamics of indigenous survival and resistance in the era of America's early nationhood. Apess's life intersects with multiple aspects of indigenous identity and existence in this period, including indentured servitude, slavery, service in the armed forces, syncretic engagements with Christian spirituality, and Native struggles for political and cultural autonomy. Even more, Apess offers a powerful and provocative voice for the persistence of Native presence in a time and place that was long supposed to have settled its "Indian question" in favor of extinction. Through meticulous archival research, close readings of Apess's key works, and informed and imaginative speculation about his largely enigmatic life, Drew Lopenzina provides a vivid portrait of this singular Native American figure. This new biography will sit alongside Apess's own writing as vital reading for those interested in early America and indigeneity."--Provided by publisher